Phantom-based assessment of motion and needle targeting accuracy of robotic devices for magnetic resonance imaging-guided needle biopsy - Antoniou, Anastasia; Nikolaou, Anastasia; Evripidou, Nikolas; Georgiou, Andreas; Filippou, Antria; Zinonos, Vasiliki; Giannakou, Marinos; Chrysanthou, Antreas; Ioannides, Cleanthis; Damianou, Christakis A. (My University, 2023)
Background:The current study proposessimple methodsfor assessingthe per-formance of robotic devices intended for Magnetic ResonanceImaging (MRI)‐guided needle biopsy. Methods:In‐housemade agar‐based breast phantoms containingbiopsy targetsservedasthemaintoolintheevaluationprocessofanMRIcompatiblepositioningdevice comprising a needle navigator. The motion accuracy of mechanical stages was assessed by calliper measurements. Laboratoryevaluationof needle targeting included a repeatability phantomtest and a laser‐based method. The accuracy andrepeatability of needle targeting was also assessed by MRI. Results: The maximum error of linear motion for steps up to 10 mm was 0.1 mm. Needle navigation relative to the phantomand alignment with the various biopsy targets were performed successfully in both the laboratory and MRI settings. The proposed biopsy phantoms offered tissue‐like signal in MRI and good haptic feed-back during needle insertion. Conclusions: The proposed methods could be valuable in the process of validating the accuracy of MRI‐guided biopsy robotic devices in both laboratory and real environments.
Keywords: MRI-guided; Agar phantoms; Breast biopsy; Motion accuracy; Needle targeting; Robotic device